Is there an intrahousehold 'flypaper effect'?: evidence from a school feeding program - Jacoby, Hanan (International Food Policy Research Institute, 1997)
Are public transfers targeted toward children largely neutralized by the household, as the theory of altruism implies, or is there an intrahousehold “flypaper effect” whereby such transfers “stick” to the child? This paper studies the impact of a school feeding program on child caloric intake in the Philippines. Because children are interviewed on school days and nonschool days, and because some schools offer a feeding program and others do not, the dietary impact of the program is identified under mild restrictions. The empirical results confirm an intrahousehold flypaper effect; indeed, they indicate virtually no intrahousehold reallocation of calories in response to the feeding program. In poorer households, however, children’s gains from the program appear to be “taxed” more heavily.